2004
DOI: 10.1152/ajpregu.00042.2004
|View full text |Cite
|
Sign up to set email alerts
|

Role of ERK1/2 in uterine contractility and preterm labor in rats

Abstract: The present study tested the hypothesis that ERK activation is an essential step in the onset of labor in a rat model of preterm labor. The administration of RU-486, an antiprogesterone agent, to rats induced preterm delivery 22.2 +/- 0.24 h after treatment. Changes in basal signaling events were studied in myometrial tissue from CO(2)-euthanized rats. Rats treated with RU-486 displayed a dramatically increased in vitro uterine contractility compared with gestational stage-matched, sham-treated rats. In vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 45 publications
3
43
0
Order By: Relevance
“…the elevated levels of myometrial ERK phosphorylation in late gestation, and the delayed labor caused by inhibition of the ERK pathway in RU486-treated rats (Li et al 2004), we hypothesize that this is an important signaling pathway that is activated as part of the parturition process. Increased ERK phosphorylation may remodel the myometrium into a contractile phenotype by modulating gene expression via activation of transcription factors (Yoon & Seger 2006) and/ or by altering the contractile apparatus via phosphorylation of cytoskeletal proteins including hCaD, paxillin, and FAK (Yoon & Seger 2006).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…the elevated levels of myometrial ERK phosphorylation in late gestation, and the delayed labor caused by inhibition of the ERK pathway in RU486-treated rats (Li et al 2004), we hypothesize that this is an important signaling pathway that is activated as part of the parturition process. Increased ERK phosphorylation may remodel the myometrium into a contractile phenotype by modulating gene expression via activation of transcription factors (Yoon & Seger 2006) and/ or by altering the contractile apparatus via phosphorylation of cytoskeletal proteins including hCaD, paxillin, and FAK (Yoon & Seger 2006).…”
Section: Discussionmentioning
confidence: 92%
“…In pregnant rats, the abundance of activated ERK in myometrial cells increases with gestation (Oldenhof et al 2002, Serrano-Sanchez et al 2008 and labor onset (Li et al 2003). In animals induced to deliver preterm (PT) by administration of the progesterone receptor antagonist RU486, concurrent inhibition of ERK signaling delayed preterm labor and decreased myometrial contractility (Li et al 2004). These data emphasize the potential importance of this pathway in the regulation of myometrial smooth muscle contractility.…”
Section: Introductionmentioning
confidence: 96%
“…Animals were maintained in a virus-and parasite-free barrier facility and exposed to a 12-h light/dark cycle. To evaluate the effect of Erk inhibition on growth plate maturation and apoptosis, wild-type mice were treated twice daily from 18 to 21 days with 100 mg/kg U0126 or vehicle (12) and killed on day 21 or 31.…”
Section: Methodsmentioning
confidence: 99%
“…More recent studies have suggested that mitogen-activated protein (MAP) kinases may also impact on contractile responses in airways [64,[77][78][79] and other types of smooth muscle [80,81]. In particular, MLC20 are the proposed substrate of extracellular signal-regulated kinase (ERK)1 and 2 [82][83][84].…”
Section: Adrenoceptors In the Lungmentioning
confidence: 99%